Hodgkins Lymphoma of Bone - A Rare Case Report - Mangala Gouri S R; Saraswathi G Rao; Sundaresh D.C. (Journal of Clinical and Diagnostic Research, 2014)
Primary Hodgkins lymphoma presenting as a lytic bone lesion is very rare. A 27-year-old male presented with deformity and pain in lower back region from past 1 year. X-ray and CT scan revealed T12 and L1 vertebral destruction and an osteolytic lesion with destruction of the Right Ilium. Clinically a diagnosis of giant cell tumour was made. However histopathology & Immunohistochemical evaluation helped in diagnosing the case as a classical Hodgkin’s disease of the bone.